Staff and student perceptions of internationalisation - Jackson, Elizabeth; Robson, S.; Huddart, T. (2012)
This paper presents a case study of staff and student perceptions of internationalisation in a UK university and explores the implications of the findings for the operationalisation of a transformative internationalisation strategy. The paper replicates the methodology employed by Robson and Turner (2007) in a humanities faculty to elicit data in a science faculty. Data from staff and students reveals limited awareness of the university's long-standing internationalisation strategy. Findings suggest that participating staff have a rather narrow perception of internationalisation as a market driven strategy which is mainly related to the recruitment of international students. Their comments focused largely on the impacts of this recruitment strategy on their preferred academic work (and research in particular). Data from focus groups and a small-scale survey suggest that students were not aware of the internationalisation strategy, nor of the potential benefits of receiving an internationalised education, but were moderately enthusiastic about the possibility of having an internationalised experience once it was explained to them. The paper reflects on these findings in relation to the concept of transformative internationalisation and offers recommendations to facilitate staff and student engagement with the internationalization strategy as a means to achieve sustained institutional change.